We all die at the end : storytelling in the climate apocalypse - Haddow, Sam (Manchester : Manchester University Press, 2025)
As the ravages of climate change throw our future into question, many of our stories are turning to the subject of extinction. This book is about what they are saying and why it demands our attention.
Front matter -- Cover -- Half Title -- Title Page -- Copyright Page -- Dedication -- Epigraph -- Contents -- Acknowledgements -- A note on spoilers -- Prologue -- Growing up in this dying world -- Parenting in the end times -- Last battles of the sexes -- The swallowing green -- Fungal bogeymen -- End gaming -- Our ruins -- Epilogue -- References -- Index
Description based upon online resource; title from PDF title page (viewed March 21st, 2025).
Includes bibliographical references and index.
JSTOR
Keywords: End of the world in literature; Climatic changes in literature; Fin du monde dans la littérature.; Climat -- Changements, dans la littérature.